Pengaruh Digital Marketing, Kualitas Pelayanan dan Daya Tarik Wisata Terhadap Minat Berkunjung Wisatawan di Museum Karst Indonesia - Amiroh Luthfiyah ‘Abidah; Muzakar Isa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of digital marketing, service quality, and tourist attraction on visit intention at the Museum Karst Indonesia. The research employed a quantitative approach based on a positivistic paradigm, where data were analyzed using the Partial Least Squares (PLS) method. Primary data were collected through questionnaires distributed to 200 respondents selected using a purposive sampling technique, while secondary data were obtained from literature studies. Data analysis included evaluating measurement and structural models to assess validity, reliability, and relationships among variables. The findings indicate that digital marketing, service quality, and tourist attraction have a positive and significant influence on visit intention. It is recommended that the museum enhance digital marketing, train employees to improve service quality, and maintain tourist attractions. Future studies are suggested to increase the sample size and explore other variables to broaden insights into factors affecting visit intention.